Antioxidative and neurotoxicity effects of acute and chronic exposure of the estuarine polychaete Hediste diversicolor to paracetamol - Barbosa, Inês (2022)
The presence of anthropogenic drugs in the aquatic ecosystems is a reality nowadays, and a large number of studies have been reporting their putative toxic effects on wildlife. However, the majority of the studies published so far uses standard organisms, whose probability of becoming in contact with drugs in real scenarios of contamination is at least, low. The use of autochthonous organisms in ecotoxicity testing is thus mandatory, and the present study aimed to assess the feasibility of assessing oxidative based stress responses (enzymatic defenses, such as catalase, glutathione-s-transferases, and lipid peroxidation; neurotoxicity as an indirect outcome of oxidizing conditions) on a polychaete species, Hediste diversicolor, after being acutely and chronically exposed to the widely employed drug paracetamol. H. diversicolor showed to be responsive to paracetamol exposure. Data obtained after acute exposure to paracetamol showed that no antioxidant adaptive response was established, but cholinesterasic activity was enhanced. On the contrary, long term exposure of H. diversicolor individuals to paracetamol resulted in clear pro-oxidative effects, with catalase and cholinesterase inhibition, and a significant reduction in the levels of lipoperoxidation. Considering that some of the tested levels (especially those of the chronic test) were already reported in the wild, the here-obtained results are of high environmental significance. In addition, chronic exposure regime yielded more significant results, with important modification of more parameters, suggesting that realistic conditions of exposure are more suited for an integrated assessment of toxicity of drugs in aquatic organisms.